Latest Developments in Polypoidal Choroidal Vasculopathy: Epidemiology, Etiology, Diagnosis, and Treatment. Issue 3 (May 2020) - Chaikitmongkol, Voraporn; Cheung, Chui Ming Gemmy; Koizumi, Hideki; Govindahar, Vishal; Chhablani, Jay; Lai, Timothy Y.Y.
Abstract : Abstract: Polypoidal choroidal vasculopathy (PCV) is a condition characterized by multiple, recurrent, serosanguineous pigment epithelial detachments, and neurosensory retinal detachments due to abnormal aneurysmal neovascular lesions. It is generally considered as a variant of neovascular age-related macular degeneration, but there are some differences between the clinical presentation, natural history, and treatment response between patients with PCV and typical neovascular age-related macular degeneration patients. Over the past decade, new research and technological advancements have greatly improved our understanding of the PCV disease process and the management of PCV. This review aims to summarize the recent research findings to highlight the epidemiology, pathogenesis, genetics, the application of various diagnostic tools for PCV, and the available treatment options for PCV.